Investigating modifiable risk factors associated with ideal cardiovascular health among cancer survivors: a scoping review - Wing Lam Tock; Yujia Tang; Lise Gauvin (Cardio-Oncology)
Abstract Background Cancer survivors are at higher risk of developing cardiovascular diseases and face worse morbidity and mortality outcomes than the general population. The American Heart Association (AHA) introduced the Life’s Essential 8 framework, encompassing eight modifiable risk factors and lifestyle behaviors for maintaining ideal cardiovascular health (CVH). Although this framework is well-established for predicting CVH in the general population, studies on its association with cardiovascular outcomes among cancer survivors remain scattered across the literature. Objective This review maps existing literature surrounding modifiable risk factors, lifestyle behaviors, CVH, and cardiovascular outcomes among cancer survivors to take stock of what is known, identify methodological strengths and weaknesses, and propose promising research directions. Methods A scoping review was conducted to identify studies examining different dimensions of ideal CVH in adult cancer survivors. Measurement methods of ideal CVH metrics, and determinants associated with CVH were examined. Results Twenty-two articles met eligibility criteria. Of which, 82% (n = 18) were published in or after 2020. Fourteen studies (about 64%) followed the AHA’s framework to conceptualize ideal CVH. Higher scores on ideal CVH are linked to better cardiovascular outcomes among cancer survivors with associations noted for social inequalities and neighborhood environmental factors, underscoring the complexity of CVH determinants in this population. Conclusions Research on ideal CVH among cancer survivors appears to have accelerated in recent years, yet many gaps remain to orient clinical and public health practice. Promising research directions include expanding investigations into pre-diagnosis CVH, addressing disparities in CVH across diverse populations, and conducting longitudinal studies to clarify causal pathways between lifestyle behaviors, cancer treatments, and cardiovascular outcomes.